HZSM-5 Catalyst for Cracking Palm Oil to Gasoline: A Comparative Study with and without Impregnation - Achmad Roesyadi; Danawati Hariprajitno; N. Nurjannah; Santi Dyah Savitri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
It is important to develop a renewable source of energy to overcome a limited source fossil energy. Palm oil is a potential alternative and environmental friendly energy resource in Indonesia due to high production capacity of this vegetable oil. The research studied effect of catalyst to selectivity of biofuel product from cracking of palm oil. The catalyst consisted of HZSM-5 catalyst with or without impregnation. The research was conducted in two steps, namely catalyst synthesized and catalytic cracking process. HZSM-5 was synthesized using Plank methods. The characterization of the synthesized catalysts used AAS (Atomic Absorption Spectroscopy) and BET (Brunaueur Emmet Teller). The cracking was carried out in a fixed bed microreactor with diameter of 1 cm and length of 16 cm which was filled with 0.6 gram catalyst. The Zn/HZSM-5 catalyst was recommended for cracking palm oil for the high selectivity to gasoline. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)